2014
DOI: 10.1016/j.biomaterials.2014.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescence imaging of cancer mediated by tumor hypoxia and HIF1α/OATPs signaling axis

Abstract: Near-infrared fluorescence (NIRF) imaging agents are promising tools for noninvasive cancer imaging. Here, we explored the mechanistic properties of a specific group of NIR heptamethine carbocyanines including MHI-148 dye we identified and synthesized, and demonstrated these dyes to achieve cancer-specific imaging and targeting via a hypoxia-mediated mechanism. We found that cancer cells and tumor xenografts exhibited hypoxia-dependent MHI-148 dye uptake in vitro and in vivo, which was directly mediated by hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 48 publications
(65 reference statements)
4
126
0
Order By: Relevance
“…85 At the molecular level, organic anion-transporting polypeptides (OATPs), a group of cell membrane-bound solute carriers, have been shown to play a key role facilitating the delivery of NIRF dyes into tumor cells. 5,19,20,22,28,30 This preferential uptake of heptamethine cyanine moiety in tumor is shown to be correlated with enhanced expression of certain type of OATPs in variety of cancer cell types. There are 11 known human OATPs classified into six families and subfamilies on the basis of their amino acid sequence homologies.…”
Section: Mechanisms Of Near-infrared Fluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…85 At the molecular level, organic anion-transporting polypeptides (OATPs), a group of cell membrane-bound solute carriers, have been shown to play a key role facilitating the delivery of NIRF dyes into tumor cells. 5,19,20,22,28,30 This preferential uptake of heptamethine cyanine moiety in tumor is shown to be correlated with enhanced expression of certain type of OATPs in variety of cancer cell types. There are 11 known human OATPs classified into six families and subfamilies on the basis of their amino acid sequence homologies.…”
Section: Mechanisms Of Near-infrared Fluorescencementioning
confidence: 99%
“…Further quantitative analysis indicated a sixfold increase of MHI-148 dye uptake intensity in tumors relative to normal tissues, with coregistered tumor regions and fluorescence signals confirmed by pathologic analyses. 20 This pioneering study strongly suggests the potential clinical utility of these attractive NIRF agents.…”
Section: Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the OATP inhibitor bromosulfophthalein (BSP) suppressed the accumulation in tumor cells of IR-783 (65), MHI-148 (65,67), and IR-780 iodide (99), primarily through inhibition of OATP1B3 (67,99) (Table III). Further studies indicated that OATP1B3 expression and related MHI-148 accumulation were induced by hypoxia (67).…”
Section: Nir Imagingmentioning
confidence: 99%
“…For example, the OATP inhibitor bromosulfophthalein (BSP) suppressed the accumulation in tumor cells of IR-783 (65), MHI-148 (65,67), and IR-780 iodide (99), primarily through inhibition of OATP1B3 (67,99) (Table III). Further studies indicated that OATP1B3 expression and related MHI-148 accumulation were induced by hypoxia (67). In addition to diagnostic applications, IR-780's accumulation within tumor cells was also associated with inhibition of cell growth in vitro and of tumor recurrence in the mouse syngeneic Lewis lung carcinoma xenograft model, suggesting that IR-780 could be used as a theranostic agent for the suppression of tumor recurrence (100).…”
Section: Nir Imagingmentioning
confidence: 99%